A Fluorescence Selection Method for Accurate Large-Gene Synthesis - Kim, Hwangbeom; Han, Hyojun; Shin, Dongyun; Bang, Duhee (WILEY-V C H VERLAG GMBH, 2010)
The fundamental problem for low-cost gene synthesis is errors that occur during the synthetic process. To address this problem, we developed a practical method that exploits the fact that the predominant errors are deletions. In this method, a simple fluorescence-based readout was used to distinguish error-free synthetic DNA molecules. To do this, we constructed vectors that contained multiple cloning sites and GFP. In the vectors, the GFP gene is designed to be out-of-frame, but insertion of an in-framed synthetic DNA construct into the appropriate cloning site will lead to fluorescent cell colonies. We successfully used this method to synthesize five genes and improved the bp per error from 629 to 6552 by selecting green fluorescent colonies.
Keywords: DNA; EXPRESSION; IDENTIFICATION; SEQUENCES; CLONING; GENOME